THE IMPACT OF BREASTFEEDING ON THE HEALTH OF CHILDREN IN UKRAINE IN THE CONTEXT OF WAR AND COVID-19 PANDEMIC CONSEQUENCES - Volosovets, Olexander; Kryvopustov, Sergii; Kuzmenko, Anatolii; Chernyshova, Olga; Zabudska, Liubov; Volosovets, Tetiana; Gryshchenko, Nataliia; Chernii, Olena; Mykhno, Anastasia (Eastern Ukrainian Medical Journal, 2025)
Introduction. Among the factors that significantly affect the condition of children in the first year of life, especially in times of war and the consequences of the Covid-19 pandemic, breastfeeding occupies a special place. Objectives: to determine the correlation rank relationship between the morbidity and mortality rates of children in Ukraine under the age of one year and the duration of breastfeeding of children 1 year of life depending on the region of residence of Ukraine. Results. Indicators of the duration of breastfeeding when children reach the age of three months have a moderate positive correlation with the mortality rate due to some infectious and parasitic diseases and the mortality rate of infants due to sudden infant death syndrome, which reached statistical significance (p˂0.05). That is, the longer breastfeeding lasted, the less likely the child was to die suddenly or due to infectious factors, which is extremely important in wartime conditions. The duration of breastfeeding when children reach three months of age has a moderate positive correlation with the incidence of diseases of the genitourinary system and diseases of the musculoskeletal system in children of the first year of life, which reached statistical significance (p˂0.05). We established a moderate positive correlation between the duration of breastfeeding when a child reaches six months of age and the incidence of diseases of the skin and subcutaneous tissue in infants, which had significant statistical significance (p˂0.01). A similar nature of the relationship was also established between the duration of breastfeeding and the incidence of respiratory diseases in infants, in particular, acute respiratory viral infections, influenza, pneumonia, which also reached statistical significance (p˂0.05). Conclusions. Breastfeeding has the highest priority in its preservation and support at all levels of influence and in its maximum possible increase in duration in order to ensure the proper development of children even in the extremely difficult conditions of our country today.